Spatiotemporal Characteristics of Soil Conservation and Protection Vacancies at Ganzhou City of Jiangxi Province - Zhou Junxin; Cai Meifang; Guo Fusheng; Huang Zhiqiang; Zhai Jiancheng (Shuitu baochi tongbao)
[Objective] The spatiotemporal pattern of soil conservation was studied and the protection vacancy areas were identified in order to provide references for regional development planning and ecological protection. [Methods] The study was conducted with data from Ganzhou City of Jiangxi Province. We used the integrated RUSLE model, the InVEST model, other ecological evaluation methods, hot spot analysis, overlay analysis, and other analysis tools combined with protection vacancy theory to analyze the space-time evolution characteristics of soil and water conservation from 2000 to 2020. We compared the existing protection areas, and identified potential priority protection areas. [Results] ① The spatial distribution of soil conservation services in Ganzhou City generally showed higher in the surrounding areas, and lower in the middle area, The most important areas were concentrated in the Luoxiao Mountains, Jiulian Mountains, Wuyi Mountains, and Yushan Mountains, with an average annual total soil conservation of 8.46×108 t. ② The spatial characteristics of the water conservation function were also generally characterized by higher in surrounding areas, and lower in middle area. The most important areas were concentrated in the upper reaches of Meijiang River basin, Pingjiang River basin, Beiling River basin, Youjiang River basin, and Taojiang River basin, as well as Wuyi Mountains to the east of Mianjiang River basin and Xiangshui River Basin. The water conservation depth averaged over many years was 213.48 mm. ③ The areas with significant soil and water conservation functions in Ganzhou City had strong spatial correlations. Compared with the existing natural reserves, the protection vacancy area was 6 155.54 hm2. There were several obvious areas with no protection around them that were located in the north of Xingguo County, the northeast of Shicheng County, the northwest and southeast of Ruijin City, and the middle of Quannan County, the southeast of Anyuan County, and the west of Xunwu County. [Conclusion] Climate factors, land use changes, and topographic and geomorphic conditions were important factors affecting the spatial and temporal differentiation of soil and water conservation functions in Ganzhou City. Ecological protection and restoration strategies should be adopted for the protection of vacant areas and functionally degraded areas.